Overexpression of DNAJB6 promotes colorectal cancer cell invasion through an IQGAP1/ERK‐dependent signaling pathway. Issue 10 (7th July 2014) - Zhang, Tong‐Tong; Jiang, Yan‐Yi; Shang, Li; Shi, Zhi‐Zhou; Liang, Jian‐Wei; Wang, Zheng; Zhang, Yu; Hao, Jia‐Jie; Jia, Xue‐Mei; Xu, Xin; Cai, Yan; Zhan, Qi‐Min; et al.
Abstract : DNAJB6 is a member of the heat shock protein 40 (Hsp40) family. We here investigated the clinical correlation and biological role of DNAJB6 overexpression in colorectal cancer (CRC). The expression of DNAJB6 protein was examined in 200 cases of colorectal adenocarcinomas by immunohistochemistry (IHC) technology. Gene transfection and RNA interference were performed to determine the effect of DNAJB6 expression on the invasion of CRC cells and to explore the underlying molecular mechanisms in vitro and in vivo. Overexpression of DNAJB6 was found in 39% (78/200) of the CRC tissues, especially in tumors at pT4 as compared with at pT1–3 ( P = 0.02). A Kaplan–Meier survival analysis revealed a correlation between DNAJB6 expression and overall survival (OS) times ( P = 0.003). Multivariate analysis confirmed that DNAJB6 overexpression was an independent prognostic factor for CRC ( P = 0.002). RNA interference‐mediated silencing of the DNAJB6 gene inhibited the invasion of CRC cells in vitro were accompanied by a significant reduction in the protein levels of IQ‐domain GTPase‐activating protein 1 (IQGAP1) and phosphorylated ERK (pERK). An in vivo assay showed that inhibition of DNAJB6 expression decreased the lung metastases of CRC cells. IHC analysis of serial sections showed that there was a positive correlation between DNAJB6 and IQGAP1 expression in primary CRC tissues ( P = 0.013). The data suggest that DNAJB6 plays an important oncogenic role in CRC cell invasion by up‐regulating IQGAP1 and activating the ERK signaling pathway and that DNAJB6 may be used as a prognostic marker for CRC. © 2014 Wiley Periodicals, Inc.